Comparison of different clean-up procedures for the determination of N-methylcarbamate insecticides in vegetable matrices by high-performance liquid chromatography with UV detection - Nunes, G. S S; Ribeiro, M. L.; Polese, L.; Barcelo, D. (Elsevier B.V., 1998)
Several clean-up procedures which included the use of glass chromatography columns (silica gel, alumina, Florisil, silanized Celite-charcoal), Sep-Pak cartridges and standard solutions were compared for the determination of the following N-methylcarbamate (NMC) insecticides: aldicarb, carbaryl, carbofuran, methomyl and propoxur. According to recovery results of the compounds after elution in a glass column, the most efficient systems employed 4.6% deactivated alumina and a silanized Celite-charcoal (4:1) as adsorbents, using dichloromethane-methanol (99:1) and toluene-acetonitrile (75:25) mixtures, respectively, as binary eluents. The recoveries of the compounds studied varied from 84 to 120%. Comparable recoveries (75-100%) for Sep-Pak cartridges in normal phase (NH2, CN) and reversed phase (C-8) were observed. Different temperatures were tested during the concentration step in a rotary evaporator, and we verified a strong influence of this parameter on the stability of some compounds, such as carbofuran and carbaryl. Recovery studies employing the best clean up procedures were performed at the Brazilian agricultural level in potato and carrot samples; Validation methodology of the US Food and Drug Administration was adapted for the N-methylcarbamate analysis. Their recoveries ranged between 79 and 93% with coefficients of variation of 2.3-8%. (C) 1998 Elsevier B.V. B.V.
Keywords: sample preparation; vegetables; food analysis; pesticides; carbamates